Board independence and corporate performance: Evidence from Malaysia - Ponnu, C.H.; Karthigeyan, R.M. (Academic Journals, 2010)
One of the key provisions of the Malaysian Code on Corporate Governance is the requirement for inclusion of outside or independent directors on the board. The recent corporate scandals that have rocked the nation provide evidence of the failure of this provision to prevent these scandals from occurring. Though the Malaysian Code on Corporate Governance has been in place since 2000, it raises the question of the appropriateness of the provision as a bulwark against corporate misdeeds. The code is based on the United Kingdom's experience as set out in the Cadbury Report. Could a code based on the Anglo-Saxon experience suit the need of this country's business environment? This research, thus, addresses empirically, the effectiveness of the provision for outside or independent directors as provided for in the Malaysian Code of Corporate Governance on the governance of Malaysian firms. The analysis was performed by monitoring the changes in corporate performance with the inclusion of these outside directors. The sample for this study comprises of firms listed on Bursa Malaysia (formerly known as Kuala Lumpur Stock Exchange) for the year ending 2006. Results show that there is no convincing evidence that the provisions as outlined in Malaysian Code of Corporate Governance as regards outside directors have any positive effect on corporate performance.